Distinct position of chaotic pulse trains observed in Malaysia - Hamzah, Muhammad Noh; Gomes, Chandima (Universiti Putra Malaysia Press, 2017)
This paper presents the chaotic pulse train (CPT) waveforms of the vertical electric field generated by lightning observed in Malaysia. Focusing on the position where these electric field changes occur in a number of cloud to ground (CG) flashes, these CPTs were detected in different ways of occurrences, durations, intensities and amplitudes. Seventy-six chaotic pulse trains were found in this study from a sum of 172 CG flash records from three thunderstorm days. The fast field antenna was employed to do the field measurements. As opposed to the typical occurrence of chaotic pulse trains prior to subsequent strokes as reported in the literature, this study has found chaotic pulse trains occurring in different places along the CG electric field waveforms.